UNRAVELLING THE COMPLEXITIES OF THE INDIA-CHINA BORDER CONFLICT: A COMPREHENSIVE ANALYSIS - Khan, Zahid Yousuf; Bhat, Shabir Ahmad; Ishfaq Ahmad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The India-China border conflict is a longstanding and very complicated territorial dispute with significant historical, cultural, and strategic dimensions. This paper provides a comprehensive analysis by delving into the historical events and factors that have contributed to the emergence and persistence of the conflict. It investigates the competing territorial claims over Aksai Chin and Arunachal Pradesh, highlighting the legal, historical, and geopolitical arguments presented by both the countries. The study evaluates the strategic implication of the conflict in contemporary geopolitics, including its impact on regional stability, alliances, and great power dynamics. It also analyses the patterns and mechanisms of escalation and de-escalation observed in the conflict, including military manoeuvres, diplomatic exchanges, and crisis management efforts. Finally, the paper explores potential pathways for resolving the tensions through diplomatic negotiations, confidence-building measures, and regional cooperation initiatives. Understanding these issues allows the paper to provide meaningful policy recommendations to lessen tensions and promote peace and stability in the region. The study shows that the roots of the conflict trace back to early 20th-century British and Russian expansions in Central Asia, with the McMahon Line and Aksai Chin remaining significant flashpoints. The strategic implications extend beyond the bilateral relationship, affecting regional and global power dynamics. Through a detailed understanding of the conflict, this research aspires to identify viable solutions for one of Asia’s most enduring territorial disputes. The steps to resolve the conflict should include bilateral negotiations, regional cooperation, and international involvement for long term bilateral, regional and international peace and stability respectively.